Corn genotypes and crop seasons on the rate of putative haploids with the expression of gene R1-navajo - Silva, Hingrid Ariane da; Scapim, Carlos Alberto; Vivas, Marcelo; Amaral Júnior, Antonio Teixeira; Pinto, Ronald José Barth; Vivas, Janieli Maganha Silva; Rossi, Robson Marcelo; Baleroni, Alessandra Guedes (Pesquisa Agropecuaria Brasileira, 2020)
The objective of this work was to evaluate the influences of the factors corn (Zea mays) genotypes, crop seasons, endosperm texture, genetic background, and genetic basis on putative haploid rates (PHRs) according to the expression of gene R1-navajo (R1-nj). Forty-one corn genotypes were evaluated as pollen receptors, in crosses with the Krasnodar haploid inducer, in two crops (summer and winter), in the municipality of Maringá, in the state of Paraná, Brazil. The experimental design was completely randomized with ten replicates (ears). The response variable analyzed was the PHR, determined by the proportion of putative haploids, obtained through the R1-nj marker, in relation to the number of diploid seeds in each ear. Subsequently, generalized linear models were used to choose the one best fit to explain the PHR in function of the tested factors. Crop seasons, genotypes, and the crop seasons x genotypes interaction affected significantly the PHR, showing the dependence of these factors on the expression of the phenotypic marker based on anthocyanin pigmentation and determined by gene R1-nj. The number of clusters formed by the genotypes was different in each crop season. Ten genotypes showed higher rates in summer than in winter. Endosperm texture, genetic basis, and genetic background did not affect the PHR.